Geochemometric approach to groundwater quality and health risk assessment of heavy metals of Yankari Game Reserve and its environs, Northeast Nigeria - Jabbo, Josiah Nuhu; Mohd Isa, Noorain; Aris, Ahmad Zaharin; Ramli, Mohammad Firuz; Abubakar, Mohammed Bello (Elsevier, 2022)
A popular eco-tourist destination happy haven, renowned for its distinctive groundwater springs, wildlife population and endowed with notable archeologic monuments and other appealing characteristics, thus the need for a baseline survey of the physiochemical measurements to ascertain the concentrations of major cations and heavy metals (Cd, Co, Cr, Cu, Fe, Li, Mn, Ni, and Pb)), their distribution across the sampling locations and to investigate the origin of Potentially Toxic Elements (PTEs) due to threats from anthropogenic and geogenic processes to its quality to evaluating its suitability for drinking, and the risk imposed on human health through the use of Water Quality Index (WQI), Hazard Quotient (HQ) and Hazard Index (HI). Concentrations of forty-one water samples from twenty natural springs, fifteen boreholes, five hand-dug wells, and a stream a were detected. Nine heavy metals (Fe, Mn, Li, Cd, Co, Cr, Cu, Pb, and Ni) were analysed with Flame Atomic Absorption Spectrometry (FAAS) and the data using different multivariate statistical approaches. Five component types; 24.40%, 14.50%, 12.10%, 9.64% and 9.24% extracted accounted for 69.79% total variance. The dominant variables derived from PCA's five components indicated the influence of the weathering of anhydrous carbonate, which released major cations and the PTEs. Calculated HQs and HI for adults and children were generally less than one (HQ < 1), indicating less or no potential carcinogenic, except for a heavy metal Cd. It exhibits an HQ and HI > 1, for children ingesting water from all the water sources. Hand-dug wells and surface water from the stream had HQ and HI > 1 for Cd for adults, which may not be harmful but with overtime exposure and may require monitoring; otherwise, it may pose more threats to adults and children with time.